M2e-based influenza vaccines with nucleoprotein: a review - Tan, Mei Peng; Tan, Wen Siang; Mohamed Alitheen, Noorjahan Banu; Yap, Wei Boon (Multidisciplinary Digital Publishing Institute, 2021)
Discovery of conserved antigens for universal influenza vaccines warrants solutions to a number of concerns pertinent to the currently licensed influenza vaccines, such as annual reformulation and mismatching with the circulating subtypes. The latter causes low vaccine efficacies, and hence leads to severe disease complications and high hospitalization rates among susceptible and immunocompromised individuals. A universal influenza vaccine ensures cross-protection against all influenza subtypes due to the presence of conserved epitopes that are found in the majority of, if not all, influenza types and subtypes, e.g., influenza matrix protein 2 ectodomain (M2e) and nucleoprotein (NP). Despite its relatively low immunogenicity, influenza M2e has been proven to induce humoral responses in human recipients. Influenza NP, on the other hand, promotes remarkable anti-influenza T-cell responses. Additionally, NP subunits are able to assemble into particles which can be further exploited as an adjuvant carrier for M2e peptide. Practically, the T-cell immunodominance of NP can be transferred to M2e when it is fused and expressed as a chimeric protein in heterologous hosts such as Escherichia coli without compromising the antigenicity. Given the ability of NP-M2e fusion protein in inducing cross-protective anti-influenza cell-mediated and humoral immunity, its potential as a universal influenza vaccine is therefore worth further exploration.